Pulmonary langerhans cell histiocytosis masquerading as tuberculosis in an infant. - Senanayake, M. P.; Mettananda, S.; De Silva, M. V. (Taylor & Francis, 2011)
A 4-month-old infant presented with continued fever, unresolving bronchopneumonia and household contact with sputum-smear-positive tuberculosis (TB) and showed marginal improvement on anti-TB chemotherapy. Recurrent pneumothorax prompted the clinical diagnosis of TB to be revised. High-resolution CT scan of the chest and open lung biopsy confirmed the diagnosis of pulmonary Langerhans cell histiocytosis. Treatment with prednisolone and vinblastin resulted in settling of fever and resolution of respiratory symptoms and signs. In communities where the prevalence of TB is high, unusual presentations should prompt consideration of alternative diagnoses.